Chemotherapy Utilization in Men with Advanced Penile Cancer. Issue 1 (15th January 2022) - Chang, Edward; Holt, Sarah; Montgomery, Bruce; Wright, Jonathan
Abstract: Introduction: Although studies using mixed insurance populations suggest that chemotherapy use in men with advanced penile cancer (PC) is low, it is unclear what regimens are being utilized. In this study, we use a database of insured patients to better understand specific chemotherapy utilization in men with PC. Methods: This is a retrospective cohort study of patients with stage IIIB or IV PC in the Surveillance, Epidemiology, and End Results-Medicare database (2004–2015). Standard of care (SOC) chemotherapy was defined by the National Comprehensive Cancer Network® guidelines: 4 cycles of paclitaxel, ifosfamide and cisplatin or 5-fluorouracil with cisplatin in the neoadjuvant, adjuvant or primary setting. We calculated what proportion of patients receive SOC or any chemotherapy within 2 years of diagnosis and analyzed what factors were associated with receiving chemotherapy. Results: Our study included 147 patients—48 stage IIIB and 99 stage IV. Of these patients, 49 (33%) received chemotherapy. Less than 5% of men received SOC. About 10% received SOC chemotherapy but an insufficient number of cycles. Married men were more likely to undergo chemotherapy (OR 3.4, 95% CI 1.5–7.8). Less than 5% of the 24 Black or Hispanic patients received chemotherapy compared to 37% of white patients (p <0.001). Conclusions: Only a third of men with stage IIIB/IV PC underwent chemotherapy. Less than 5% of men received complete guideline-based regimens. Whether this is driven primarily by patient or provider factors is unknown, although social determinants of health may play a role. These data highlight the difficulty for patients with PC to get chemotherapy.